Parkinson's Disease: Extracellular Nanomatrix‐Induced Self‐Organization of Neural Stem Cells into Miniature Substantia Nigra‐Like Structures with Therapeutic Effects on Parkinsonian Rats (Adv. Sci. 24/2019) - Zhang, Shiqing (Adv Sci (Weinh), 2019)
In article number https://doi.org/10.1002/advs.201901822, King Wai Chiu Lai, Zhifeng Huang, Ken Kin Lam Yung, and co‐workers develop a biocompatible silica sculptured in nanozigzags by glancing angle deposition. The nanomatrix induces self‐organization of neural stem cells into miniature substantia nigra‐like brain structures, which could deliver early and progressive amelioration in Parkinsonian rats. These results provide significant insight into novel cell therapies for Parkinson's disease. [Image: see text]